Water Level Measurement Altitude Trainer Integrated With Human Machine Interface - Ade Gafar Abdullah; Agung Pramudiantoro Putra (Universitas Pendidikan Indonesia, 2017)
This research aims to design a trainer simulator wake height of the water level measurement using microcontroller arduino mega integrated with Human Machine Interface (HMI). This tool is designed to describe a working system of water level elevation measurements as a learning medium HMI. By using a microcontroller arduino mega, all processes in both input and output can be integrated to the HMI using a 7-inch LCD screen.